Management Criteria Evaluation of Lithuanian Football Academies’ Certification System (Baltic Journal of Sport and Health Sciences, 2024)
Background. There is a tendency in the football environment to assess and classify youth football organisations on a national scale to make their activities more efficient, raise the level of football and talent development, and increase competition in the context of international football. Considering the practices of Georgia and Latvia, Lithuania has started testing the certification of football academies since 2021. During the testing stage, it was observed that the certification project helped youth football organisations to improve the quality of their activities and competencies – after a year, the certification system was started to be applied to all Lithuanian football academies. As of 2022, higher certification criteria have been applied to football organisations, which the future of our country depends on.Methods. Analysis of scientific literature, content analysis of official documents, semi-structured interview (qualitative research).Results. Football organisations that participated in the certification process and received the highest evaluations are monitoring the certification process, examining the necessity of criteria through the prism of project improvement, constantly discussing with certification experts, and providing insights into the areas where the certification process should be improved. The research revealed what action plan would bring a higher level of quality to develop and improve a higher level of football in Lithuania.Conclusions: The evaluation of the Lithuanian football academy certification system revealed strengths and weaknesses; Top-rated football academies are committed to improving themselves and football development in the country; Organisations face documentation difficulties and lack of clarity in criteria descriptions; Considering the problems in certain areas of limitations, solutions must be found through the support of Lithuanian Football Federation and governmental institutions; the study provides unique perspective and insights to improve certification system and raise the level of Lithuanian football.Keywords: Lithuanian football, certification system, management criteria, certification system development.